2018
DOI: 10.1177/000313481808400106
|View full text |Cite
|
Sign up to set email alerts
|

Curative Resection for Hilar Cholangiocarcinoma: Single-Center Experience with Long-Term Follow-Up

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…At the time of this review, a total of 13 studies were found in which HPD was used for treatment of either GC or ECC. HPD represents the only curative treatment for GC and ECC (the latter also known as ‘Klatskin tumour’, or ‘hilar cholangiocarcinoma’ or ‘peri-hilar cholangiocarcinoma’), having extensive horizontal tumor spread with infiltration of the hepatic hilum and the intrapancreatic bile duct, due to the tissue invasion via the lymphatics and perineural spaces[ 3 , 4 ]. While CG and ECC represent the main indication for HPD, in a minority of cases this surgical approach has been used also in patients having benign disease, liver cancer, neuroendocrine tumours (especially pancreatic neuroendocrine tumor metastatic to the liver) and other malignancies[ 8 , 9 , 12 - 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of this review, a total of 13 studies were found in which HPD was used for treatment of either GC or ECC. HPD represents the only curative treatment for GC and ECC (the latter also known as ‘Klatskin tumour’, or ‘hilar cholangiocarcinoma’ or ‘peri-hilar cholangiocarcinoma’), having extensive horizontal tumor spread with infiltration of the hepatic hilum and the intrapancreatic bile duct, due to the tissue invasion via the lymphatics and perineural spaces[ 3 , 4 ]. While CG and ECC represent the main indication for HPD, in a minority of cases this surgical approach has been used also in patients having benign disease, liver cancer, neuroendocrine tumours (especially pancreatic neuroendocrine tumor metastatic to the liver) and other malignancies[ 8 , 9 , 12 - 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gallbladder cancer (GC) and extrahepatic cholangiocarcinoma (ECC) are tumours with dismal prognosis. Resection provides the only chance of cure, although this kind of surgery is technically challenging due to the complexity of biliary and vascular anatomy of the hepatobiliary-pancreatic region, and the necessity to perform extended hepatic resection[ 1 - 4 ]. In general, biliary cancers have various modes of local extension, including a ‘horizontal spread’ involving the entire extrahepatic biliary tree.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, the use of preoperative biliary drainage and portal vein embolization in curative-intent surgery for PHC is higher in East Asian surgical centres (27)(28)(29)(30)(31)(32)(33)(82)(83)(84)(85), compared to the Western centres (34,35,40,43,52,79,(86)(87)(88)(89)(90).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…90) (table 2). In the present series major hepatectomies were used in 80.7% of patients, and portal vein resection and reconstruction was performed in 16.7% of patients.The use of preoperative biliary drainage in recent series of Western patients with curative-intent surgery for PHC is reported to be 45% -88.2%, while portal vein embolization was used in 0% -25.5%(34,35,43,52,79,(86)(87)(88)(89)(90)(92)(93)(94)(95) (table 2). In the present cohort biliary drainage was used in 26% of patients and no patient…”
mentioning
confidence: 99%